Concordance between Antimicrobial Resistance Phenotype and Genotype of Staphylococcus pseudintermedius from Healthy Dogs - Joaquim Viñes; Norma Fàbregas; Daniel Pérez; Anna Cuscó; Rocío Fonticoba; Olga Francino; Lluís Ferrer; Lourdes Migura-Garcia (MDPI AG, 2022)
Staphylococcus pseudintermedius, a common commensal canine bacterium, is the main cause of skin infections in dogs and is a potential zoonotic pathogen. The emergence of methicillin-resistant S. pseudintermedius (MRSP) has compromised the treatment of infections caused by these bacteria. In this study, we compared the phenotypic results obtained by minimum inhibitory concentration (MICs) for 67 S. pseudintermedius isolates from the skin of nine healthy dogs versus the genotypic data obtained with Nanopore sequencing. A total of 17 antibiotic resistance genes (ARGs) were detected among the isolates. A good correlation between phenotype and genotype was observed for some antimicrobial classes, such as ciprofloxacin (fluoroquinolone), macrolides, or tetracycline. However, for oxacillin (beta-lactam) or aminoglycosides the correlation was low. Two antibiotic resistance genes were located on plasmids integrated in the chromosome, and a third one was in a circular plasmid. To our knowledge, this is the first study assessing the correlation between phenotype and genotype regarding antimicrobial resistance of S. pseudintermedius from healthy dogs using Nanopore sequencing technology.